Campuran Laston Untuk Lapis Antara Menggunakan Agregat Gamping - Leksminingsih Leksminingsih (Direktorat Bina Teknik Jalan dan Jembatan, 2005)
Indonesia has big sources of limestones which have not been used in asphalt mixes, therefore, their use for road pavement construction should be socialized. The goal of the research is to find out the propertes and comparison of limestone aggregates from two different locations namely Wonogiri and Tasikmalaya, West Java. The performance of Asphaltic concrete with ACâ€“binder specification for limestone aggregates from Tasikmalaya was compared with Bina Marga II Specification for limestone aggregates from Wonogiri. The result showed that limestone aggregatesex Tasikmalaya have the optimum asphalt content of 6.55%, Marshall stability 52% higher, dynamic stability increased to 23% and stiffness modulus at the temperature of 24% higher than standard aggregates ex Sumedang. Limestone aggregates ex Wonogiri have the optimumasphalt content of 5%, Marshall stability 15% higher, dynamic stability increased to 8,7% and stiffness modulus at the temperature of 25Â°C increased to 43,4% compared to standard aggregates ex Banjaran. The research revealed that both aggregates performed better than standard aggregates. It means that limestone aggregates provide skid resistance to disintegration of road pavement.